Ground-based near-infrared remote sounding of ice giant clouds and methane - Tice, D (2014)
The ice giants, Uranus and Neptune, are the two outermost planets in our solar system. With only one satellite flyby each in the late 1980’s, the ice giants are arguably the least understood of the planets orbiting the Sun. A better understanding of these planets’ atmospheres will not only help satisfy the natural scientific curiosity we have about these distant spheres of gas, but also might provide insight into the dynamics and meteorology of our own planet’s atmosphere. Two new ground-based, near-infrared datasets of the ice giants are studied. Both datasets provide data in a portion of the electromagnetic spectrum that provides good constraint on the size of small scattering particles in the atmospheres’ clouds and haze layers. The broad extent of both telescopes’ spectral coverage allows characterisation of these small particles for a wide range of wavelengths. Both datasets also provide coverage of the 825 nm collision-induced hydrogen-absorption feature, allowing us to disentangle the latitudinal variation of CH4 abundance from the height and vertical extent of clouds in the upper troposphere. A two-cloud model is successfully fitted to IRTF SpeX Uranus data, parameterising both clouds with base altitude, fractional scale height, and total opacity. An optically thick, vertically thin cloud with a base pressure of 1.6 bar, tallest in the midlatitudes, shows strong preference for scattering particles of 1.35 μm radii. Above this cloud lies an optically thin, vertically extended haze extending upward from 1.0 bar and consistent with particles of 0.10 μm radii. An equatorial enrichment of methane abundance and a lower cloud of constant vertical thickness was shown to exist using two independent methods of analysis. Data from Palomar SWIFT of three different latitude regions (30